Towards a data-driven military A multi-disciplinary perspective - Pijpers, Peter B.M.J; Voskuijl, Mark; Beeres, Robert (Leiden University Press, 2023)
Towards a Data-Driven Military: A Multidisciplinary Perspective assesses the use of data and information on modern conflict from different scientific and methodological disciplines, aiming to generate valuable contributions to the ongoing discourse on data, the military and modern warfare. Part one, 'Military Systems and Technology',, approaches the theme empirically by researching how data can enhance the utility of military materiel and subsequently accelerate the decision-making process. Part two, 'War Studies', takes a multidisciplinary approach to the evolution of warfare, while the third part, 'Military Management Studies', takes a holistic organisational and procedural approach. Based on their scientific protocols and research methods, the three domains put forward different research questions and perspectives, providing the unique character of this book.